Dendritic cell biology in human cytomegalovirus infection and the clinical consequences for host immunity and pathology - Gredmark-Russ, Sara (Landes Bioscience, 2012)
Human cytomegalovirus (HCMV), a member of the herpesvirus family, establishes life-long persistence and latency after primary infection and can be reactivated later in life. In immunosuppressed patients, it is an important pathogen that can cause severe disease. HCMV is also thought to play a causative role in inflammatory diseases and cancer. The virus can infect different immune cells, including dendritic cells (DCs) and can take advantage of host immune functions to avoid immune recognition. These characteristics have sparked major interest in understanding HCMV and its interaction with immune cells and their relevance to disease pathogenesis. In this review, we focus on the complex host-pathogen relationship between HCMV and DCs, including the persistence of the virus in these cells, their function in the immune response to HCMV infection and the potential clinical consequences of HCMV infection in DCs.